Experimental study on local scour around submerged monopile under combined waves and current. (15th November 2021) - Lyu, Xing; Cheng, Yongzhou; Wang, Wensen; An, Hongwei; Li, Youyun
Abstract: Submerged pile foundation have been widely used in ocean. Plenty of promising research concentrate on local scour around mono-pile or pile groups. Yet submerged situation remains unawareness. Based on a series of laboratory flume experiments, local scour in the vicinity of the submerged monopile foundation under the action of combined wave and current are studied in this research. During the experiments progress, simultaneously the scour depth and pore pressure in the sand are measured under various hydrodynamic factors. Then 3D laser scanner is applied to capture the scour topography. The experimental results indicate that with decreasing submergence ratio ( h c / D ), or declining monopile height, the horseshoe vortex and vortex shedding weaken accordingly. Subsequently, the scour rate, radius and depth perform a correspondingly reducing tendency. Considering dimensionless parameters Keulegan-Carpenter number and Froude number ( KC and Fr ), the data analysis centered on the relative equilibrium scour depth ( s/D ), demonstrate a satisfactory consistency comparing to previous research results. Under the action of combined wave and current, the pore pressure around the monopile presents periodic sinusoidal variation. The pore pressure exerts an upward seepage force inside the sand which bearing the cyclic loading. Hence, the sand-bed express extra susceptibility and vulnerability to scour induced by combined wave and current. Highlights: Experimental investigations of scour around submerged monopile are carried out under various wave and currents. The local depth and the morphology of the scour hole were captured by 3D laser scanner. Pore pressure response inside seabed were measured with micro-sensors. The influence factors, such as Fr, KC and the submergence ratio hc /D are discussed. These results may provide reference to the design and construction of the submerged structures.